Genetic and morphological diversity analysis of lime and acidic Citrus spp. from two germplasm collections in Thailand - Paweena Chuenwarin; Sunanta Wiphuwathinee; Ratchadawan Bowonchaikittikun; Ramonnaporn Chuenjit; Wuttipong Srinual; Sirilak Napa; Wachiraya Imsabai; Anyamanee Auvuchanon (Agriculture and Natural Resources, 2021)
Lime and other acidic Citrus fruits are cultivated and bred for commercial uses as ingredients in several types of foods and beverages as flavorings. To improve new cultivars through a better understanding of the genetic relationships of this type of Citrus, germplasm collections (50 accessions) were investigated consisting of Mexican lime, citron, lemon, Tahiti lime, kaffir lime, calamansi and finger lime obtained from the Tropical Fruit Research and Development Center and Ta Auan Lime Orchard, Thailand. Sequence-related amplified polymorphism (SRAP) markers and morphological traits were identified and used to classify the lime species and other acidic Citrus spp. cultivated in Thailand. Eleven SRAP markers were used to evaluate polymorphism and 340 polymorphic amplicons were observed with an average polymorphism information content of 0.45. Based on the results from the SRAP markers and population structure analysis, the 50 accessions of acidic Citrus trees in Thailand were divided into four subpopulations and classified into eight clusters that clustered the same types of Citrus together. Principal component analysis of acidic Citrus morphological data indicated close relatedness in accordance with genotypic data. This study revealed that Mexican lime (C. aurantifolia (Christm.) Swingle), the primary commercial lime grown in Thailand, has narrow genetic diversity. To improve lime varieties in the future, these findings can aid breeders in selecting more genetically diverse acidic Citrus species to cross with Mexican lime.